Bacteriuria in older adults triggers confusion in healthcare providers: A mindful pause to treat the worry - Eva M. Amenta; Robin L.P. Jump; Barbara W. Trautner (Cambridge University Press, 2023)
The evidence base for refraining from screening for or treating asymptomatic bacteriuria (ASB) in older adults is strong, but both practices remain prevalent. Clinical confusion over how to respond to a change from baseline, when to order a urinalysis and urine culture, and what to do with a positive urine culture fuels unnecessary antibiotic use for ASB. If the provider can take a mindful pause to apply evidenced-based assessment tools, the resulting increased clarity in how to manage the situation can reduce overtreatment of ASB.